Development of Students’ e-Worksheet on Environmental Change using PRIMA Learning Model to Improve Science Process Skills - Makalunsenge, Dina Sulistiani; Yusuf, Frida Maryati; Lamangantjo, Chairunisah (FKIP Universitas Lampung, 2022)
This study objective was to describe the validity, practicality and effectiveness of Blended Learning-based Student Worksheets on environmental change materials using the PRIMA Learning model in improving Science Process Skills. This study was conducted at SMA State 1 Batudaa Pantai Senior High School and employed ADDIE development model. The result demonstrated that the developed blended learning-based worksheets were valid for use in schools with the assessment result from validators in the score range of 89.2% - 91.7% (extremely valid). Students’ worksheet practicality can be observable from several stages, including student activities, learning implementation, student responses’ results with an average value of 91.25%, 100%, 93% (perfectly acceptable). Further, Students’ worksheet effectiveness test based on the N-Gain score obtained a result of 0.68 (Effective), and the percentage N-Gain value (%) is 68 (moderately effective).In conclusion, the said learning is valid, practical, and effective in learning biology in class X SMA 1 Batudaa Pantai Senior High School.Keywords: students’ worksheet, environmental change, science process skills.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1337-1346